2017
DOI: 10.1002/ieam.2005
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in water toxicity associated with current use pesticides in three California agriculture regions

Abstract: Regulation of agriculture irrigation water discharges in California, USA, is assessed and controlled by its 9 Regional Water Quality Control Boards under the jurisdiction of the California State Water Resources Control Board. Each Regional Water Board has developed programs to control pesticides in runoff as part of the waste discharge requirements implemented through each region's Irrigated Lands Regulatory Program. The present study assessed how pesticide use patterns differ in the Imperial (Imperial County)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Initial concerns related to toxic benthic cyanobacteria have focused on human health risks (Wood et al ), the risk to terrestrial animals (in particular stock and dogs; Mez et al ; Gugger et al ), and impacts on higher trophic level species (Wood et al ); however, these toxins can also affect macroinvertebrates (DeMott et al ; Toproska et al ). The potential for toxicity to arthropod macroinvertebrates is of particular concern because some of the neurotoxic cyanotoxins bind to neuroreceptors targeted by currently used pesticides (Aboal et al ; Da S. Ferrão‐Filho and Kozlowsky‐Suzuki 2011) that are known to impact aquatic ecosystems (Dirzo et al ; Morrissey et al ; Anderson et al ). The potential for cyanontoxins and current‐use pesticides to have similar effects on standard test species could confuse our determination of the causes of aquatic ecosystem toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Initial concerns related to toxic benthic cyanobacteria have focused on human health risks (Wood et al ), the risk to terrestrial animals (in particular stock and dogs; Mez et al ; Gugger et al ), and impacts on higher trophic level species (Wood et al ); however, these toxins can also affect macroinvertebrates (DeMott et al ; Toproska et al ). The potential for toxicity to arthropod macroinvertebrates is of particular concern because some of the neurotoxic cyanotoxins bind to neuroreceptors targeted by currently used pesticides (Aboal et al ; Da S. Ferrão‐Filho and Kozlowsky‐Suzuki 2011) that are known to impact aquatic ecosystems (Dirzo et al ; Morrissey et al ; Anderson et al ). The potential for cyanontoxins and current‐use pesticides to have similar effects on standard test species could confuse our determination of the causes of aquatic ecosystem toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the past and on-going water survey programs setup in California have yielded an important and valuable amount of data on the occurrence of pyrethroids. These studies demonstrated that one or two pyrethroids were frequently present in whole water samples, and that the dominant active compound differed in space and time (both years and seasons), reflecting the distinct agricultural targets, shifts in usages, and emissions from urban pest control [11,19]. A metadata analysis gave the integrated view that cyhalothrin and bifenthrin were the compounds most frequently exceeding Regulatory Threshold Levels in surface freshwater of the USA and reached higher maxima in concentration [2].…”
Section: Occurrence and Composition Of Various Pyrethroids In Water Ementioning
confidence: 99%
“…The occurrence of individual pyrethroids varies geographically and seasonally as a response to agricultural use [19], and the consequent emission to the water, but probably also to different seasonal and site degradation potential. In Hospital Creek, a tributary of the San Joaquin River (Central California), bifenthrin was responsible for the greatest part of the toxicity of particles, whereas cyhalothrin was the prominent toxicant of particles in Ingram Creek, another tributary located less than 50 km away from the former [14].…”
Section: Occurrence and Composition Of Various Pyrethroids In Water Ementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, agricultural watersheds can manifest spatial variation in water quality impairment due to differences in land use types, soils, nutrient inputs, and agricultural activities across the landscape (Demcheck et al 2004;Mueller-Warrant et al 2012;Poudel et al 2013). The impairment of physical and chemical properties of surface waters can negatively impact biological communities due to, for example, hypoxia and harmful algal blooms (Zhou et al 2008;Broussard and Turner 2009;Riseng et al 2011;Budria 2017;Breitburg et al 2018), increased levels of fecal bacteria (Brendel and Soupir 2017), elevated levels of suspended sediment (Basnyat et al 1999;Riseng et al 2011), or the presence of pesticides (Echeverría-Sáenz et al 2012;Anderson et al 2014Anderson et al , 2018.…”
mentioning
confidence: 99%